Food Price Volatility and Vulnerability in the Global South: Considering the Global Economic Context - Jennifer Clapp (Third World Quarterly, 2009)
Most official analyses of the recent food price crisis have focused on the market fundamentals of supply and demand for food as key explanatory factors. As a result, most of the policy recommendations emanating from the major international institutions include measures to boost supply and temper demand. In this paper I argue that international macroeconomic factors played a key role in fostering both price volatility and vulnerability, and as such they need to be recognised. With respect to the recent price volatility, the weak US dollar and speculation on agricultural commodities futures markets greatly influenced agricultural prices. With respect to price vulnerability, global economic forces played an important role in dampening production incentives in the world's poorest countries over the past 30 years, leading to a situation of food import dependence. Policy responses to the food crisis must consider the role of these broader international macroeconomic forces—both in the immediate context and their longer term impact.